An Analysis of Grammatical Error in Justin Bieber's Song Lyrics - Alin Hera Julieta (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2023)
ABSTRACTA language is a communication tool used by every human being in everyday life. People used their language to communicate with each other to help deliver the information. Meanwhile, Indonesians lack grammar, especially to studying from unreliable sources, such as listening to songs. This research is trying to analyze the grammatical error in Justin Bieber’s song lyrics and identify the most frequent type of errors found in Justin Bieber’s song lyrics. This is descriptive qualitative research and the data instrument used in this research is data analysis. The result shows that there were three types of grammatical errors contained in Justin Bieber's song lyrics, such as Subject-Verb Agreement, Indefinite Pronouns, and Prepositions. The grammatical error contains 7 grammatical errors found in the subject-verb agreement, 5 grammatical errors found in the Indefinite Pronouns, and 1 grammatical error found in the preposition. However, the subject-verb agreement is the most frequent grammatical error used in Justin Bieber’s song lyrics.Keywords: Grammatical Error, Justin Bieber’s Songs, Lyrics